AN ANALYTICAL VIEW OF USING E-COMMUNICATION TOOLS IN PROMOTING OF SELECTED PILGRIM TOURISM SITES IN SLOVAK REPUBLIC - FERENCOVÁ, Martina; MIŠENČÍKOVÁ, Veronika; KOT, Sebastian (Journal of Environmental Management and Tourism, 2016)
Using promotional tools with an emphasis on e-communication instruments is an integral part of modern marketing strategy of companies, firms and organisations. An analysis of their use in the area of culture – aimed at cultural heritage monuments and pilgrimage sites - isalso topical taking into consideration all target groups. This article examines the use of e-communication tools with an emphasis on social networks when promoting selected cultural heritage monuments and pilgrimage sites according to a designed e- communication model. The results of the analysis indicate a below average and insufficient use of e-communication tools, mainly social networks when promoting selected cultural heritage monuments and pilgrimage sites in the Prešov region in the east of the Slovak Republic.
Keywords: cultural heritage monuments; pilgrimage sites; promotional tools; social networks